catena-Poly[[aquatrimethyltin(IV)]-{[trimethyltin(IV)]-μ(3)-thiophene-2,5-dicarboxylato}] - Yang, Sheng-Xiang (International Union of Crystallography, 2009)
In the title compound, [Sn(2)(CH(3))(6)(C(6)H(2)O(4)S)(H(2)O)](n), each of the two crystallographically independent Sn atoms exhibits a distorted trigonal–bipyramidal coordination geometry formed by two O and three C atoms. The coordinated water molecule plays an important role in crystal packing consolidation via O—H⋯O hydrogen bonding.